Mercados monetários: uma análise comparada de Brasil, Estados Unidos da América e Reino Unido - Camilo, Rafael de (2018)
The objective of this research is, through a comparative analysis with international references, to present the specificities of the institutional structure of the brazillian money market. In order to do so, the first step is to describe, from a general perspective, the institutional structure of the money markets. Based on this description, the specificities of the monetary markets of Brazil, the United States of America and the United Kingdom are exposed. With such description, a comparative analysis is carried out between the brazillian money market and researched international markets to verify possible similarities and divergences in their institutional structures. From the results found it is possible to suggest improvements to the institutional design of the brazillian money market, in the case BCB wishes to approximate to the market operation of the international experiences: to stimulate the private asset market; to reduce the rates on reserve requirement; the use of two rates for reserve requirement, one lower for companies with small inventory of assets and other for companies with large inventory; differentiated rates of interest to standing facilities, one for normal times and others, lower, for the last day of the maintenance period; to increase the number of counterparties in the open market operations; and to improve the dynamism between National Treasury of Brazil and Brazilian Central Bank.